Planning Post-Lockdown Reopening of Libraries: A Review of Literature - Asundi, A. Y.; Uplaonkar, Shilpa S. (Journal of Information and Knowledge, 2020)
The majority of libraries across the world in as many as 188 countries have been shut down due to COVID-19 pandemic. The situation in India is the same. Most educational institutions have been closed since 24th March. Libraries have also been closed during this period. The libraries would open on 1 June 2020, and most library managers would be thinking, what to do after reopening? Where to start, what should be the priorities, what security measures need to be put in place, etc. During this period users’ services as also the normal functioning of libraries have been affected. The IFLA and many LIS professional bodies across the world have suggested several key remedial measures on the reopening of libraries. The published literature in this regard is quite extensive and voluminous. This paper has attempted a review of literature and to provide links to these papers for libraries to make use of them when in need.